2010
DOI: 10.4049/jimmunol.1001051
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TCR Ligation Triggers Digital Activation of NF-κB

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
62
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 18 publications
7
62
1
Order By: Relevance
“…It has been proposed that digitization of NF-kB signaling occurs upstream or at the level of the TCR such that only strong TCR ligands will generate efficient signal to induce gene expression (27). Instead of this, the data presented in this article suggest that even weak TCR signals can produce efficient NF-kB signaling that persists during the immune response.…”
Section: Mut T Cells Recover Nf-kb Signaling In Response To Low-affincontrasting
confidence: 45%
“…It has been proposed that digitization of NF-kB signaling occurs upstream or at the level of the TCR such that only strong TCR ligands will generate efficient signal to induce gene expression (27). Instead of this, the data presented in this article suggest that even weak TCR signals can produce efficient NF-kB signaling that persists during the immune response.…”
Section: Mut T Cells Recover Nf-kb Signaling In Response To Low-affincontrasting
confidence: 45%
“…T cells then initiate bulk membrane movements involving active actin remodeling, spreading, and formation of an extensive contact area within minutes (14,15). This may be viewed as a global event involving the whole cell (16) and a hallmark of analog-to-digital signal processing (17,18). Also, strong evidence supports the hypothesis that extensive morphological changes may act as early reporters of the triggering of a specific activation program (19,20).…”
mentioning
confidence: 68%
“…Previous studies have reported all-or-nothing activation of signaling molecules that control cytokine gene expression, such as NF-κB [5], NFAT1 [6], Ras [7] and ERK [8]. Ras and ERK have been suggested to acquire digital behavior by positive feedback regulation [7,9].…”
mentioning
confidence: 99%